QUALITATIVE MORPHOLOGICAL ANALYSIS AND DOCUMENTATION OF FEATHERS OF FLYING AND AQUATIC BIRDS - SREEJITH, PARAMESWARA PANICKER; PRASAD, CHAITHRA; PREETHI, S.; SURESH, SURYA; MON, T. M. BINU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Feathers are the most characteristic attribute of birds and display a wide variety of morphologies. Functions of feathers are universal in birds; they embody thermal insulation, temperature regulation, physical protection against the surroundings, feeling, look, and visual signs. They are also essential for flight and water repellency. The morphological differences for the flying and aquatic birds were made, and different level examinations and comparisons were documented. Different feather types were identified based on their morphological characteristics, and they are categorized. For the study of the ultra-structure of feathers, stereo examination and Scanning Electron Microscope(SEM)examination were carried out. Four orders of flying birds and two orders of aquatic birds were selected for the study. There is no such difference between the stereo images and SEM images of flying and aquatic birds. The shape, composition, arrangement, pattern etc., play a major role in the aerodynamics flight of flying birds and the swimming and flying ability of aquatic birds. By comparing different flying birds' orders, we observe that the barbules are asymmetrically distributed, and the interlocked barbules were closely arranged in the barbs of birds that go for flying due to their changing habitat and those birds which completely depend upon terrestrial habitats. Birds which do not go for flying have symmetrically distributed barbules, and interlocked barbules were centerally arranged. Most barbules were loosely organized. Changes in environmental conditions and habitats play an essential role in making a difference in the barbules arrangement. This factor influence the behavior of swimming and flying birds.